IMPLEMENTASI APLIKASI JASA PENGIRIMAN BARANG BERBASIS ANDROID PADA CV. EXPRESS TRI’YO MUJUR - Yudianto; Sigit Birowo (Institut Bisnis dan Informatika Kwik Kian Gie, 2021)
This research is made because of many weakness owned by freight forwarding company in its business process. Vehicle reservation done by phone is not effective if there is too many requests at the same time. Delivery information’s distribution is still lacking ad goods claim problem which reducing the company’s profit. Android is an operating system for mobile device based on Linux which including operating system, middleware and application. Android based mobile devices can be used to access information from whenever and wherever. Programming language used is Java and PHP for accessing database. The database used is MySQL. Data collection technique in this research is obtained by observation non-participant, direct interview and literature study. To analyze and designing application, the flow and process in this goods delivery information system are described by data flow diagram, use case diagram, sequence diagram, activity diagram, and Entity Relationship Diagram. The result produced by this research is an Android based goods delivery information application, starting from the vehicle reservation until claim items submission. And on the admin’s side is produced a vehicle data management web which is owned by delivery service company and information distribution process given to the people who’s using goods delivery service. Freight forwarding information system can facilitate CV. Express Tri’yo Mujur in processing goods delivery service. Freight forwarding information can be easily accessed by service users. Claim process is no more viewed as one of the problem which reduce the company’s profit because the standard rule is already written before the goods delivery request can be done, and with the evidence on the claim data there will be no party suffer from losses. Keywords : Expedition, Service Delivery, Application, Android, Web.